Thrombopoietin Promotes Cell Proliferation and Attenuates Apoptosis of Aplastic Anemia Serum-Treated 32D Cells via Activating STAT3/STAT5 Signaling Pathway and Modulating Apoptosis-Related Mediators. (11th February 2021) - Qian, Juan; Cao, Xin; Shen, Qian; Cai, Yi-feng; Lu, Wei; Yin, Hong; You, Xue-fen; Liu, Hong
The present study aimed to investigate the effect and possible mechanism of recombinant human thrombopoietin (rhTPO) on mouse 32D cells (a mouse myeloid progenitor cell line) treated with serum from patients with aplastic anemia and to elucidate the potential mechanism of rhTPO in the treatment of aplastic anemia. After treatment with aplastic anemia serum, the apoptotic rate of 32D cells was increased and the proliferation of 32D cells was significantly inhibited. rhTPO reduced the apoptotic rate and promoted the proliferation of 32D cells, while rhTPO failed to restore the cell proliferation of 32D cells from aplastic anemia serum group to the normal level as compared to that from the normal serum group. The phosphorylation level of STAT3 protein was higher, and the phosphorylation level of STAT5 protein was lower in 32D cells from aplastic anemia serum group than that in normal serum group. After rhTPO treatment, the phosphorylation level of STAT3 protein in aplastic anemia serum group was decreased and the phosphorylation level of STAT5 protein was increased. The expression levels of Survivin and Bcl-2 were significantly decreased in 32D cells from aplastic anemia serum group, which were significantly increased after rhTPO treatment. The expression level of Bax protein in 32D cells from the normal serum group after rhTPO treatment was significantly decreased; while the mRNA expression level of Bax was not affected by rhTPO. The expression levels of Bax mRNA and protein were significantly up-regulated in 32D cells from aplastic anemia serum group, which was significantly decreased by rhTPO treatment. In conclusion, our results indicated that aplastic anemia serum impaired proliferative potential and enhanced apoptosis of 32D cells. Further mechanistic studies revealed that rhTPO promoted cell proliferation and attenuated apoptosis of aplastic anemia serum-treated 32D cells via activating STAT3/STAT5 signaling pathway and modulating apoptosis-related mediators.